Media Pendidikan Politik: Analisis Perspektif Pemuda dan Alternatifnya dalam Konteks Covid-19 - Oki Anggara; Agus Rendra (SAP (Susunan Artikel Pendidikan), 2023)
This article aims at finding and figuring out what political education media is interesting and needed for youth so that the substance and function of political education can run as optimally as possible. The COVID-19 pandemic that has occurred in recent years has had a significant impact on the implementation of political education as a logical consequence of limiting activities outside home. The media used before the pandemic was not optimal in building political understanding. This makes the community (including youth) need other alternatives that are suitable for pandemic conditions. This study uses mixed methods with a sequential explanatory strategy. The participants in this study were youth, practitioners and experts. Quantitative data analysis was carried out using descriptive and qualitative statistics using the Miles and Huberman model analysis. The research findings showed that political education was seen as something related to state affairs by today's youth. In the context of the COVID-19 pandemic, political education media that is seen as interesting and needed for youth is indirect political education media, such as social media which contains interesting, interactive, up-to-date, and light audio-visual content so that it can reach many youth widely and more desirable. In addition, Korean drama is seen as an alternative media for political education.